Back of beyond ebook - Box, C.J (Cassie Dewell, 2011)
Edgar Award-winning and New York Times bestselling author C.J. Box delivers a thriller in Back of Beyond about a troubled cop trying to save his son from a killer in Yellowstone, now reissued with additional bonus content including an introduction from the author. Cody Hoyt, although a brilliant cop, is an alcoholic struggling with two months of sobriety when his friend Hank Winters is found burned to death in a remote mountain cabin. At first it looks like the suicide of a man who's fallen off the wagon, but Cody knows Hank better than that. As Cody digs deeper into the case, all roads lead to foul play. After years of bad behavior with his department, Cody is in no position to be investigating a homicide, but he will stop at nothing to find Hank's killer. When clues found at the scene link the murderer to an outfitter leading tourists on a multiday wilderness horseback trip into the remote corners of Yellowstone National Park—a pack trip that includes his son Justin—Cody is desperate to get on their trail and stop the killer before the group heads into the wild. In a fatal cat-and-mouse game, where it becomes apparent the murderer is somehow aware of Cody's every move, Cody treks into the wilderness to stop a killer hell-bent on destroying the only important thing left in his life. *BONUS CONTENT: This edition of Back of Beyond includes a new introduction from the author and a discussion guide